Dividend commitment in firm bylaws and capital structure change. (1st November 2020) - Cheng, Linyin; Wang, Guojun; Wang, Yuetang; Yang, Dan
Abstract: Dividend policies can predict changes in capital structure. We focus on a unique setting, namely, dividend commitment emerging from a new dividend policy in China, and explore its relation to leverage. We find a commitment to increase dividends is associated with a subsequent reduction in leverage, and this negative relation is enhanced in firms without preliminary conditions specified for their commitments or with greater dividend smoothing in previous periods. Robustness tests support the main findings. Further analysis addresses four internal mechanisms that play essential roles in the above link, and we provide further details about how leverage is reduced.